Topical KOH 5% solution: a valuable option for treatment of warts in children - Chiriac, A.; Solovan, C.; Brzezinski, P. (European Journal of Pediatric Dermatology, 2014)
Case report. A healthy 8-year-old boy with a newly diagnosed middle size common wart on the third left finger was seen in consultation. A 5% KOH (potassium hydroxide) solution was recommended topically once daily at night under occlusive dressing for seven consecutive days. At the end of the treatment we observed no complaints from the child or members of the family, no side-effects and good tolerability. Clinical examination (Fig. 1) proved a clear-cut demarcation of the wart from the surrounding hyperkeratotic tissue; there were no signs of inflammation. The topical treatment with 5% KOH solution was discontinued and simple emollients and hygiene measures were recommended for the following days, resulting in "cutting-off" of the entire lesion without sequelae.